Hubungan Pengetahuan dan Persepsi Lansia dalam Mengikuti Vaksinasi covid 19 di Puskesmas - Chichi Hafifa Transyah; Daeng Ramadhan Salim; Intan Permata Sari (Jurnal Amanah Kesehatan, 2024)
The low achievement of the covid-19 vaccination in the elderly is coused because the elderly do not know about the covid-19 vaccination and have various perceptions regarding the covid-19 vaccination. The elderly said they did not believe in Covid-19, did not believe in the Covid-19 vaccine, and were afraid to die after being injected with the vaccine. The purpose of this study was to determine the relationship between knowledge and perceptions of the elderly in participating in the covid-19 vaccination. Type of reseach is quantitative with analytical descriptive design using a cross sectional design. The study was conducted at the Anak Air Padang Health Center from May to August 2022. The sampling technique was accidental sampling with a large sample taken 1 week as many as 30 people. The data were analyzed univaritely and bivariate with chi-square statistic test. The results of univariate study were obtained who did not follow the covid-19 vaccination 18 (60.0%), knowledge less as much as 29 (96.7%), and who have a negative perception 19 (63.3%). The results of the bivariate is no relationship between the knowledge of the elderly in participating in the covid-19 vaccination (p=0.40) and there is a relationship between the perception of the elderly in participating in the covid-19 vaccination (p=0.000). The conclusion is that there is no relationship between knowledge in participating in the covid-19 vaccination, but the perception of the elderly is very related in participating in the covid-19 vaccination. Researchers hope that the elderly can follow the covid-19 vaccination. Keyword : Knowledge; Perceptions; Covid-19 Vaccination;